Psychological distress and attitudes toward seeking professional psychological help among Omani nurses: Strategies for nursing practice - Mohammed Ghalib Qutishat (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: This study investigated the psychological distress and attitudes toward seeking professional psychological help among Oman's nurses, highlighting the importance of changing negative attitudes toward mental health among healthcare professionals. Nurses face difficult circumstances and serve as role models. Creating supportive environments can improve treatment quality and public awareness and reduce social stigma, ultimately contributing to better care and quality of life. MATERIALS AND METHODS: This study used a cross-sectional design with a convenience sampling approach. A sample of 205 nurses working in Oman completed the study questionnaires, including a sociodemographic questionnaire, the attitude toward seeking professional psychological distress scale, and the Kessler Psychological Distress Scale. The survey was distributed between May and June 2023. RESULT: The study found that most participants had moderate psychological distress (43.22%, n = 67) and a low attitude toward seeking professional psychological help (66.67%, n = 48). There were significant differences in distress based on gender (P < 0.001), marital status (P < 0.001), and working department (F = 3.140, P = 0.004), while attitude had significant differences based on gender (P < 0.001) and marital status (P < 0.001). The study also found no significant correlation between psychological distress and attitudes toward seeking help among Oman's nurses (T (1, 204) = 0.019, P = 0.985), with a r2 of 0.005. CONCLUSION: Nurses must be trained to handle stress and job strain from terminally ill patients, complex cases, and difficult situations. They should prioritize psychological assistance as a sign of strength and self-awareness as it demonstrates stability and self-awareness in nursing. This can be promoted by obtaining education, enhancing healthcare accessibility, and providing a support system.